2006
DOI: 10.1590/s1519-69842006000600013
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval development of Jundiá (Rhamdia quelen, Quoy & Gaimard, 1824, Pisces, Teleostei), a South American Catfish

Abstract: The jundiá (Rhamdia quelen, Quoy & Gaimard) is an endemic South American fish species. Because this species supports cold winters and grows faster during warm months, it has begun to be viewed as an ideal species for fish production in southern South America. In the present study, jundiá oocytes used were obtained by extrusion from females after hormone injection. Soon after hydration, the eggs were transferred to 50 L conic glass incubators, with constant and controlled water influx. Samples of fertilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 15 publications
(5 reference statements)
2
18
0
10
Order By: Relevance
“…That fact may be observed when compared with other species, such as Rhamdia quelen, which exhibits oocytes with average diameter from 1.0mm (Pereira et al, 2006) (Bombardelli et al, 2006). Sanches et al (2010), studying the same species, observed the VAP of 58.67±9.01µm s -1 and progression of 1,202.80±163.89µm 15 seconds after activation, unlike S. parahybae, which despite exhibiting larger eggs, also exhibits higher values of VAP and PROG, and even so needs higher inseminating doses.…”
Section: Discussionmentioning
confidence: 84%
“…That fact may be observed when compared with other species, such as Rhamdia quelen, which exhibits oocytes with average diameter from 1.0mm (Pereira et al, 2006) (Bombardelli et al, 2006). Sanches et al (2010), studying the same species, observed the VAP of 58.67±9.01µm s -1 and progression of 1,202.80±163.89µm 15 seconds after activation, unlike S. parahybae, which despite exhibiting larger eggs, also exhibits higher values of VAP and PROG, and even so needs higher inseminating doses.…”
Section: Discussionmentioning
confidence: 84%
“…The embryonic period of species using different reproductive strategies can be much longer. For example, the embryonic period of Rhamdia quelen (Quoy & Gaimard, 1824) lasted 30 h 5 min at 24 °C (Pereira et al, 2006), and that of Parauchenipterus galeatus (Linnaeus, 1766), lasted 64 h at a water temperature of 27-28 °C (Sanches et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Existe um sincronismo entre machos e fêmeas durante a reprodução, que ocorre logo ao amanhecer, o macho segue a fêmea e promove alguns toques com a cabeça no seu ventre estimulando a desova (Baldisserotto & Radünz Neto 2004). Não apresenta cuidado parental e desova em locais com água limpa, calma e de fundo pedregoso (Godinho et al 1978, Gomes et al 2000, Pereira et al 2006. Os valores encontrados para a FRP (fecundidade relativa ao peso) de R. quelen nos rios Paraibuna e Grande foram próximos do apresentado para Rhamdia branneri (= R. quelen) em ambientes naturais preservados do Paraná (Paula-Souza 1978 apud Gomes et al 2000), mas foi superior ao de R. quelen em confinamento e inseminados artificialmente (Bombardelli et al 2006).…”
Section: Resultsunclassified